The Evolution of the Theory of Innovation Ecosystems in the Context of Strategisation - Petchenko, Maryna; Telnova, Hanna; Yakushev, Oleksandr; Kuzminova, Olha (Dr. Viktor Koval, 2024)
Introduction. The theory of innovation occupies one of the leading positions within the modern paradigm of economic development, as innovation is recognised as a driver of productivity improvement and cost optimisation, microeconomic stability, and macroeconomic growth. The determinants of innovation theory have become more profound, forming a synthesis with theories of economic cycles, technological development, entrepreneurship, management, and decision-making. Consequently, the theory of innovation has evolved, and the study of this process provides an up-to-date view of the theoretical foundation of innovation ecosystems. Aim and tasks. The aim is to systematise the stages of the evolution of the theory of innovation and strategic management and formalise the theoretical foundation of the modern theory of innovation ecosystems in the context of strategisation. Results. A systematic study of the genesis and ontogenesis of the theory of innovation and anagenesis of the theory of innovation ecosystem in the context of strategisation led to the determination of the characteristics of aromorphosis. Genesis and ontogenesis include the growing complexity of the innovation ecosystem and its adaptability to the changing innovation ecosystem in the long term, the dynamism of the composition of the innovation ecosystem without changing its strategic goals, the need for a second level of adaptation of the strategy of an individual actor within the strategy of the innovation ecosystem and strategic role, and increasing the integration of actors of the innovation process into systemic business processes (planning, organisation, motivation, control). Actors’ joint development within the ecosystem on mutually beneficial terms and possibilities for the strategic expansion of the innovation ecosystem locally and globally were analysed.  In addition, the externalities of the development and spread of innovative ecosystems are outlined, and their strategic orientations are formulated. Conclusions. Due to anagenesis, an innovative ecosystem based on strategising improves adaptive resistance to changes in the external environment. Aromorphosis of an innovative ecosystem within anagenesis makes it possible to consider the properties of adaptation to the changing innovative ecotope as the basis of its theoretical foundation in the long term, the dynamism of the composition of the innovation ecosystem without changing its strategic goals, and the increasing integration of innovation process actors into systemic business processes.